Valproic acid utilization among girls and women in Stockholm: Impact of regulatory restrictions. Issue 3 (13th June 2018) - Karlsson Lind, Linnéa; Komen, Joris; Wettermark, Björn; von Euler, Mia; Tomson, Torbjörn
Summary: Objective: In November 2014, the European Medicines Agency (EMA) strengthened restrictions on the use of valproic acid in girls and women of childbearing potential. The objective of this study was to determine whether there has been a change in initiations of valproic acid treatment to females after the regulatory restrictions and to assess if such changes differed between indications (epilepsy and psychiatric disorder). Methods: An interrupted time‐series analysis was conducted using all initiations of valproic acid in Stockholm, Sweden. from January 2011 to June 2017. Female and male patients aged 0–45 years with a recorded diagnosis of epilepsy and/or a psychiatric disorder were compared. Results: Before the EMA warning, a decline in trend of valproic acid initiations was seen in patients with epilepsy. After the warning, a significant decrease of valproic acid initiations was seen in women with a psychiatric disorder, but not in women with epilepsy. Significance: The regulatory warning appeared to have significantly influenced valproic acid initiations in women of childbearing age with a psychiatric disorder. No effect was seen in women with epilepsy, probably because the decline had started long before.